Effects of Single Parenthood in the Education of Children: A Case Study of Kisauni Sub County, Mombasa County - Ccabson, Ntondwe Walakisa Re (International Journal of Humanity and Social Sciences, 2024)
Purpose: The purpose of the Study is to gather useful information on the effects of single parenthood in the education of children, the study was guided by the following research question "What are the causes of single parenthood?" Literature was reviewed under the following sub headings; Causes of single Parenthood and Effects of Single Parenthood on Children Performance Methodology: The researcher employed use of survey method to gather data, simple random was used in sampling respondents. Findings: The study found out that effect of single parenthood is lack of attention with 38% followed compared to others with 05% in relation to others. Unique contribution to theory, policy and practice: the researcher recommended that County Government of Mombasa should give come up with relevant policies to address the problem in question like providing out credits to single parents and promote financial institutions that access affordable business loans to needy single parents, enabling them to develop the quality of education and life for the children and bridge the gap between such children and the well to do.